Two Transforms on Landau-Lifshitz Equations and Their Application (Journal of Partial Differential Equations, 2020)
In this paper we obtain some new results on Landau-Lifshitz equation by two explicit transforms.
Keywords: Multidimensional Landau-Lifshitz equation; discontinuous and unbounded external field; explicit transform; exact solution; weak solution